2021
DOI: 10.3390/biology10060518
|View full text |Cite
|
Sign up to set email alerts
|

2La Paracentric Chromosomal Inversion and Overexpressed Metabolic Genes Enhance Thermotolerance and Pyrethroid Resistance in the Major Malaria Vector Anopheles gambiae

Abstract: Changes in global temperature are impacting the spread/intensity of vector-borne diseases, including malaria, and accelerating evolutionary/adaptive changes in vector species. These changes, including chromosomal inversions and overexpression and/or changes in allele frequencies of thermotolerance-associated genes, may facilitate insecticide resistance through pleiotropy. This study investigated the impact of thermotolerance on pyrethroid resistance in four populations of the malaria vector An. gambiae s.l., f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…gambiae (Greppi et al, 2020), with both shown to be overexpressed/induced in thermotolerant/permethrin resistant populations of An. coluzzii (Ibrahim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…gambiae (Greppi et al, 2020), with both shown to be overexpressed/induced in thermotolerant/permethrin resistant populations of An. coluzzii (Ibrahim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These two genes were among the overexpressed genes in both heat-hardened and permethrin-resistant An. coluzzii populations from northern Nigeria (Ibrahim et al, 2021). Several ionotropic glutamate receptors were found within the 2La inversion breakpoints: IR136 (AGAP006440), IR139 (AGAP006691) and IR142 (AGAP006407).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations